Review of Different Models of Coastdown Transient in Pressurized Water - Ahmad, Shakeel; Ahmad, Idrees (The Nucleus, 2023)
Problems related to the loss of coolant flow in nuclear reactor may initiate fuel meltdown and fuel-cladding interaction (FCI) due to the overheating of fuel and are therefore of great concern in power reactor safety. Therefore, licensee must provide evidence through rigorous analyses of all conceivable flow problems that plant’s engineered safety systems (EES) have the capability to maintain fuel and cladding temperatures well below the melting point. Among the loss of flow events the flow coastdown transient is also a critical issue considered for the safety analysis of Pressurized Water Reactor (PWR), which is characterized by a sudden loss of power to the main reactor coolant pump (RCP). There has been a provision in RCP to maintain flow through reactor core for some time, immediately after the loss of power to pump, like in case of Station Blackout (SBO) due to the flywheel mechanism of RCP. However, that is inadequate for the extended times following the SBO and RCP must be powered by emergency diesel generators (EDGs) to maintain flow through the reactor core to remove heat from the fuel without any break. After the event of Fukushima, a lot of progress has been made to analyze situations, where the EDGs become inundated or unavailable. Analytical and empirical models have continuously been evolved to simulate the characteristics of pumps in such a crucial event to guide accident prevention and mitigation strategies. These models are divided into two broad categories like the short models and detailed models. The short models take into account the inertia of the flywheel, pump speed and the flow rate in core. The detail models also consider the pump characteristic curve on which homologous curves are derived and help to establish head and flow rate third degree polynomial. It has been observed that the detail models predict more accurate results in comparison with the experimental data. It has also been observed that the accuracy of the simulated results also relies on the inclusion of the pump mechanical friction losses in the model. Moreover, an attempt has been made to extend the coastdown transient analysis to predict the core outlet temperature during the course of the accident which requires an efficient solution strategy for solving models for the pump, coolant half time and the core time constant. In this article, evolution of different models has been discussed in detail.